Los Materiales - Tonucci, Francesco; Roca, Andreu (Barcelona, España : Abril, 1990)
La arcilla--El color, La madera-- Fichas
General
Traducido del francés al español
Keywords: Madera -- Arte; Color; Pintura -- Colores; Dibujo -- Técnica